Metaphysical Intersections in Frankenstein: Mary Shelley’s Theistic Investigation of Scientific Materialism and Transgressive Autonomy - Hogsette, David S. (Christianity & literature, 2011)
Frankenstein is a speculative narrative that asks: what would happen if man created human life without the biologically and relationally necessary woman and with indifference to God? What if Adam were to reject his own Creator and create life after his own fleshly or material image? Mary Shelley’s answer to these questions is not a triumphant humanist manifesto, nor is it an ironic subversion of a supposedly outmoded theistic perspective. Rather, she offers a philosophical nightmare revealing the horrific consequences of methodological naturalism taken to its logical conclusion. Frankenstein explores the ideologicalvacuum engendered by Scientific materialism and examines the spiritual bankruptcy of replacing theism with secular humanism. Victor Frankenstein’s transgressiveautonomy, grounded in scientific materialism, results in a reductionism that ultimately leads to existential despair, individual crisis, and communal disintegration.